On the influence of low-velocity impact damage on constrained-layer damping in hybrid CFRP-elastomer-metal laminates - Alexander Jackstadt; Wilfried V. Liebig; Kay A. Weidenmann; Luise Kärger (Materials & Design, 2024)
Following the principle of constrained-layer damping (CLD), fiber-metal-elastomer laminates (FMELs) offer a high potential for damped lightweight structures, overcoming the undesirable vibration characteristics of conventional lightweight materials. While proven to be versatile and efficient, the damage-tolerance of such laminates is unexplored. This study for the first time in literature addresses the damage-tolerance of this efficient damping mechanism using a combined experimental and numerical approach. Results of experimental low-velocity impact tests on different configurations of FMELs are presented. In subsequent numerical modal analyses, different types of damage, namely delaminations, intra-ply damage and permanent deformation, are modeled and their influence on the vibrational behavior is investigated. While all types of damage influence the natural frequencies and modal damping ratios with a strong mode dependency, all laminates retain a high amount of modal damping with losses typically not higher than 15%. The results obtained reveal, that CLD is an efficient intrinsic damping measure in FMELs even in the presence of different types of damage. The key contributions of this paper include the thorough experimental characterization of low-velocity impact damages in different configurations of FMELs as well as the numerical assessment of those in frequency-domain simulations.